Body Image, Eating Behaviour, and Physical Activity among Students at National Defence University of Malaysia - Azli, Mohd Syrinaz; Mohamad Rahim, Khairul Haziq; Hasan, Hosni; Khairul Ikram, Emmy Hainida (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to explore the relationship between body image, eating behaviour, and physical activity among students at the National Defence University of Malaysia (UPNM). A total of 114 students, aged between 19 to 31 years old, were requited from the National Defence University of Malaysia (UPNM). Data were collected using an online self-report questionnaire which consists of four sections; Sociodemographic Form, Body Image Avoidance Questionnaire (BIAQ), Eating Attitude Test (EAT-26), and the International Physical Activity Questionnaire (IPAQ). Almost half of the respondents have normal BMI, whereas 20.2% were underweight and 23.7% were overweight and obese. Mean body image avoidance scores for civilian students, Reserve Officer Training Unit (ROTU), and cadets were 38.88±12.39, 42.71±6.34, and 44.00±16.05, respectively. Furthermore, high physical activity level was seen the most among civilian students (72.3%) compared to (57.1%) and cadets (41.7%). Significant associations were found between body image and eating behaviour (p<0.001). No association was observed between body image with physical activity (p>0.05) and eating behaviour with physical activity (p>0.05). To conclude, the respondents with a risk of the eating disorder tend to have higher body image avoidance, and the physical activity level did not seem to be concerning body image and eating behaviour in this study.